SISTEM MONITORING SUHU KOTAK SMARTPHONE CHARGER TENAGA SURYA MENGGUNAKAN NODEMCU ESP8266 - Tolomaking, Yohanes Skifoanus Nogo; Hunaini, Fachrudin; Uhida Subhan, Moh; Siswanto, Diky (JASEE Journal of Application and Science on Electrical Engineering, 2025)
Growing energy demand and the depletion of fossil fuel resources have increased the need for sustainable alternative energy sources. Solar energy is suitable for tropical regions and can be applied to small-scale charging systems. This study designs and implements a temperature monitoring and control system for a solar-powered mobile phone charging box to maintain internal temperature stability and support battery charging performance. The system uses a NodeMCU ESP8266 microcontroller, DHT22 sensor, cooling fan, lighting load, Wi-Fi communication, and Blynk Internet of Things platform for real-time smartphone monitoring. Temperature and humidity data are collected inside the box and transmitted to Blynk, while the fan is activated automatically when the temperature exceeds the predefined threshold. Test results show that the system detected changes in operating conditions. When the fan was off and the lamp was on, the temperature was 28°C with 68.40% humidity. When the fan was on and the lamp was off, the temperature reached 30°C with 78.50% humidity. Solar panel output varied from 19.9 V, 0.393 A, and 7.834 W in the morning to 16.02 V, 0.16 A, and 2.563 W in the afternoon. These findings indicate that the proposed system can support real-time monitoring and automatic thermal control.